Community-based prevention of hepatitis-B-related liver cancer: Australian insights - Monica C Robotin; Melanie Q Kansil; Mamta Porwal; Andrew G Penman; Jacob George (The World Health Organization, 2014)
Problem Although most primary hepatocellular cancers (HCCs) are attributable to chronic viral hepatitis and largely preventable, such cancers remain a leading cause of cancer-related mortality wherever chronic hepatitis B is endemic. Approach Many HCCs could be prevented by increasing awareness and knowledge of hepatitis B, optimizing the monitoring of chronic hepatitis B and using antiviral treatments - but there are gaps in the implementation of such strategies. Local setting The "B Positive" programme, based in Sydney, Australia, is designed to improve hepatitis-B-related health outcomes among immigrants from countries with endemic hepatitis B. The programme offers information about disease screening, vaccination and treatment options, as well as optimized access to care. Relevant changes The B Positive programme has been informed by economic modelling. The programme offers culturally tailored education on chronic hepatitis B to target communities and their health practitioners and regular follow-up through a population-based registry of cases. Lessons learnt As the costs of screening for chronic hepatitis B and follow-up are relatively low and less than one in every four cases may require antiviral drugs, optimizing access to treatment seems an appropriate and cost-effective management option. The identification and accurate staging of cases and the judicious use of antiviral medications are predicated upon an informed and educated health workforce. As establishing community trust is a lengthy process, delaying the implementation of programmes against chronic hepatitis B until antiviral drugs become cheaper is unwarranted.